PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI MATEMATIS DENGAN REALISTIC MATHEMATIC EDUCATION - Bahari, Silvia (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
The Purpose of this study was to describe the improvement of studentsâ ability of problem solving and mathematical communication through Realistic Mathematics Education Approach. This is a Classroom Action Research (CAR). The participants of the research were the studentsâ of grade V which consisted of 24 students. The findings showed that the studentsâ ability of problem solving and mathematical communication have improved. The thoroughness of studentâs ability of problem solving on the first cycle just 33,33%. This result increase became 66,67% at second cycle and 87,50 at third cycle. The studentâs ability of mathematical communication also have improved by RME Approach. On the first cycle, the thoroughness just 54,17. This result increase became 62,50% at second cycle and 87,50% at third cycle. In conclusion, applying Realistic Mathematical Education Approach can improve studentsâ ability of problem solvingÂ  and mathematical communication at grade V SD No. 001/XI Kelurahan Pasar Sungai Penuh. Key Word: Problem solving, communication of mathematic, Realistic Mathematic Education